WORKSHOP PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM PEMBUATAN KONTEN PEMBELAJARAN BAGI GURU SMP NEGERI 1 PEUREULAK - Vivi Asbar; Nur Amalia Hasma; Cut Amalia Saffiera; Siti Farras Chanira (LPPM Universitas Nusa Mandiri, 2026)
This community service activity aims to improve teacher competency in utilizing Artificial Intelligence (AI) in creating learning content at SMP Negeri 1 Peureulak. Based on initial observations of 25 teachers, only 20% of teachers have ever used AI-based applications in learning, while the majority still use conventional media and are not yet able to produce AI-based learning content independently. The method used was a workshop with a theoretical and practical approach, including lectures, discussions, simulations, case studies, and independent practice. The workshop utilized several AI applications, namely ChatGPT for compiling teaching materials and evaluation questions, Canva AI for creating visual learning media, and Gamma AI for developing learning presentations. The results of the activity showed an increase in participant competency as indicated by an increase in the average score from 54.00 in the pre-test to 81.43 in the post-test with a percentage increase of 50.80%. In addition, as many as 72% of participants were able to produce AI-based learning content with a good category. The participant responses also showed a high level of satisfaction and participation throughout the activity. Thus, this workshop contributed to improving teachers' competency in utilizing AI for learning content development and has the potential to be replicated in broader contexts. Participants produced AI-assisted teaching materials, learning presentation slides, evaluation questions, and visual learning media.